The dynamic of treatment-seeking in a community sample with obsessive-compulsive symptoms: A mixed method approach - Winitra Kaewpila; Thanavadee Prachasan; Ratana Saipanish; Thanita Tantrarungroj; Fred Stevens (PLoS ONE, 2025)
Objective This mixed-method study aimed to investigate factors associated with treatment-seeking behaviors in people with obsessive-compulsive (OC) symptoms in the community and explore their experiences along the dynamic of treatment-seeking processes. Method Eighty-one subjects with OC symptoms (27 treatment seekers and 54 non-seekers) completed online questionnaires about treatment history, symptom severity, and factors influencing treatment-seeking. The characteristics of treatment seekers and non-seekers were compared using Pearson’s Chi-square and independent T-tests. Qualitative data were derived from a subset of 26 participants undergoing a follow-up telephone interview and subsequently analyzed by thematic analysis. Results Treatment seeking was associated with more severe overall OC and obsessive symptoms and more feeling out of control over the symptoms (p < .05). Qualitative analyses revealed three main themes of barriers (i.e., displacement of causation, perceived controllability, and thresholds to access treatment) intricately tied to the stages of help-seeking, from problem recognition to service utilization. The need to control was identified as a key determinant in shifting between the vicious OC-illusionary-control loop and the treatment-seeking-control loop along the dynamic of treatment-seeking processes. Conclusion The symptom severity and feeling out of control are critical factors associated with treatment-seeking among people with OC symptoms in the community. Enhancing the feeling of control could be pivotal in promoting help-seeking behaviors in this population.